دور الائتمان المصرفي الخاص في تمويل القطاع الصناعي في سورية - ضاهر حنان; أحمد رونزا (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يعد الائتمان المصرفي مصدر تمويل أساسي لجميع القطاعات الاقتصادية، وهو من أهم الخدمات التي تقدمها المصارف. تسلط هذه الورقة الضوء على الدور الذي يلعبه الائتمان المصرفي الذي تقدمه المصارف الخاصة التقليدية العاملة في سورية في تمويل القطاع الصناعي. لتحقيق غرض الدراسة تم جمع البيانات لعينة مكونة من 11 مصرفاً خاصاً. امتدت فترة الدراسة من 2006 إلى 2011. جمعت بيانات الدراسة بشكل أساسي من القوائم المالية للمصارف المدروسة. لغرض تحليل بيانات الدراسة تم استخدام أحد نماذج Panel Data وهو نموذج الانحدار التجميعي. وقد تم تحليل البيانات بالاعتماد على البرنامج الإحصائيEviews7. تم استخدام دالة الإنتاج لدراسة العلاقة بين الائتمان المصرفي المقدم من المصارف الخاصة التقليدية إلى القطاع الصناعي والناتج المحلي الإجمالي لهذا القطاع. أظهرت نتائج الدراسة أن الائتمان المصرفي المقدم من المصارف الخاصة التقليدية يؤثر بشكل إيجابي على الناتج المحلي الإجمالي للقطاع الصناعي في سورية. The banking credit is the funding source of all economic sectors; it’s one of the most important services provided by banks. This paper highlights the role of bank credit provided by traditional private banks operating in Syria in financing the industrial sector. To achieve the purpose of the study, the sample collected consists of 11 commercial banks. The study period extended from 2006 to 2011. The study data is primarily collected from the financial statements of the banks studied. For the purpose of the study, a Panel Data Model, the pooled regression model, was used for data analysis. The data were analyzed based on statistical program Eviews7. The production function was used to examine the relationship between the banking credit provided by traditional private banks to industrial sector and GDP for the sector function. Results of the study showed that the banking credit provided by traditional private banks positively affects the GDP of the industrial sector in Syria.………………………………………... 00000000000000000000000000000000000000000000000 Results of the study showed that both the capital employed in the industrial sector and the private bank credit positively affect the GDP of the industrial sector in Syria, while the number of employees in the industrial sector negatively affects the GDP of the industrial sector.